Penggunaan Bahasa Lisan Siswa Kelas XI MA Al-Asy’ariyah Bandarlampung Tahun Pelajaran 2017/2018 - Dechri Giyanis; Farida Ariyani; Eka Sofia Agustina (Jurnal Kata (Bahasa, Sastra, dan Pembelajarannya), 2019)
The purpose of this research was to describe the use of spoken language in Indonesian language learning activities of the eleventh grade students of MA Al-Asy’ariyah Bandarlampung academic year 2017/2018. The method used in this research was qualitative descriptive. The research population was 120 students. The sample of this research was all students of eleventh grade with the total of 51. Data collection techniques in this research are non-participation observation techniques, documentation, and techniques (focusing on the semple). The source of this research data was the sound recording of the students’ and  the teacher's conversations that contain a variety of spoken languages based on the standard form of words, diction, and pronunciation. The results showed that there were 161 raw conversations, and 226 conversations were not standard, from 387 data on the number of conversations using spoken language. The results of the conversational data percentage of 41.60% of students used standard spoken language, while 58.40% of students tend to ignore the standard verbal language rules.Tujuan penelitian ini untuk mendeskripsikan penggunaan bahasa lisan dalam kegiatan pembelajaran bahasa Indonesia siswa kelas XI MA Al-Asy’ariyah Bandarlampung tahun pelajaran 2017/2018. Metode yang digunakan dalam penelitian ini adalah deskriptif kualitatif. Populasi penelitian ini adalah seluruh siswa berjumlah 120. Sampel penelitian ini seluruh siswa kelas XI berjumlah 51. Teknik pengumpulan data dalam penelitian ini adalah teknik observasi nonpartisipasi, dokumentasi, dan teknik (focusing of the semple). Sumber data penelitian ini adalah rekamanan suara percakapan siswa dan guru yang mengandung ragam bahasa lisan berdasarkan bentuk baku kata, diksi, dan lafal. Hasil penelitian menunjukan bahwa terdapat 161 percakapan baku, dan 226 percakapan tidak baku, dari 387 data jumlah percakapan penggunaan bahasa lisan. Hasil persentase data percakapan  41,60% siswa menggunakan bahasa lisan baku, sedangkan 58,40% siswa cenderung mengabaikan kaidah bahasa lisan baku.Kata kunci: penggunaan bahasa lisan, pembelajaran bahasa Indonesia, dan siswa SMA.